René Bustamante, Cuauhtémoc González Pacheco, Francisco José Ruiz Cervantes, Miguel Lozano, Silvia Millán Echegaray, Francisco A. Gómezjara: Oaxaca, una lucha reciente: 1960-1978 - Terán, Marta (Revista Mexicana de Sociología, 2024)
-